Pelvic rocking exercise sebagai alternatif manajemen nyeri dysmenorrhea primer: A systematic literature review - Kirana, Magenta; Fauza, Sri Novia (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Primary dysmenorrhea is a common menstrual disorder experienced by adolescent girls and young women of reproductive age, characterized by lower abdominal cramping pain that interferes with daily activities without any underlying organic pathology. Pelvic rocking exercise is a potential non-pharmacological intervention because it is simple, inexpensive, and can be performed independently; however, the scientific evidence is still scattered and has not been systematically synthesized. Purpose: To evaluate pelvic rocking exercise as an alternative for managing pain in primary dysmenorrhea. Method: A systematic review was conducted by searching literature in PubMed, Scopus, and Google Scholar databases using keywords related to